Effect of soil water tensions on vegative and productive development of pimenta-de-macaco - De Souza, Leonardo Paula; Zocoler, João Luis [UNESP]; Bergo, E. Celso Luis (My University, 2018)
The objective of this research was to evaluate the effect of soil water tensions on vegetative and productive development for Pimenta-de-macaco (Piper aduncum) irrigated by drip system.The experimental design of randomized blocks, with five treatments (tensions 20; 40; 60 and 100 kPa and also with no irrigation) and four replications was used.Two harvests were made to quantify biomass and, consequently, essential oil extraction.The first harvest was performed when the culture reached ten months of cultivation and the second harvest after six months.In the first harvest in irrigated conditions in the last four months, only the crown diameter variable showed no significant difference among the treatments evaluated.In the second harvest, only the essential oil yield and dillapiole content in the essential oil were not influenced by the treatments.Pimenta-de-macaco has moderate tolerance to water deficit and the soil water tension recommends to initiate irrigation from 20 to 60 kPa.
Efeito das tensões da água no solo no desenvolvimento vegetativo e produtivo da pimenta-de-macaco
Keywords: Dillapiole; Drip irrigation; Essential oil; Piperaceae